When the quadratic equation 5x2 = 2 ( 2x + 3 ) is expressed in the
standard form, the constant term obtained is
(B) 6
(A) 5
(D) - 6
(C) 4
of
32
Answers
Answered by
0
Answer:
d=-6
Step-by-step explanation:
d=-6 as 5x2= 4x+6
5x2-4x-6
Answered by
0
Given : Quadratic equation 5x² = 2 ( 2x + 3 ) is expressed in the
standard form
To Find : the constant term
Solution:
Quadratic equation 5x² = 2 ( 2x + 3 )
=> 5x² = 4x + 6
=> 5x² - 4x - 6 = 0
standard form of Quadratic equation
ax² + bx + c = 0
a ≠ 0
Comparing 5x² - 4x - 6 = 0 with ax² + bx + c = 0
Hence a = 5
b = - 4
c = - 6
a is coefficient of x²
b is coefficient of x
c is constant term
Hence the constant term obtained is -6
Learn More:
Find out any two values of m so that the roots of x2 +mx -24 = 0 are ...
brainly.in/question/7533398
activity 9 finding the roots of polynomial equations find all real roots ...
brainly.in/question/12138040
Similar questions
English,
1 month ago
Social Sciences,
3 months ago
Science,
3 months ago
Hindi,
11 months ago
English,
11 months ago